Assessing family relationships through drawing: the Family Life Space - Gennari, Marialuisa; Gozzoli, Caterina F.; Tamanza, Giancarlo (Frontiers in Psychology, 2024)
The Family Life Space (FLS) is a graphic instrument that may aid the relational assessment of families. This interactive instrument involves all members of the family in a joint task, that of collectively making a drawing of their own family system and it allows the gathering of information related to the overall family organization. The FLS was originally conceived by Danuta Mostwin in the early 70s and used as an instrument for clinical intervention. After having been applied to several contexts, the present contribution aims at presenting the key indicators to use the instrument as a tool for assessing family relations. Specifically, the characteristics of the instrument that allow the gathering of relevant information at the individual, relational, and family level will be outlined. For each of these levels, the data regarding the quantity and quality of the elements in the drawing that define the family space (i.e., the number and graphic quality of the actual elements in the drawing) as well the quantity and quality of the relationships among family members and with their community at large (i.e., the number and type of lines connecting the various elements in the drawing) will be presented. The instrument can therefore provide useful insights on the following constructs: quality of life, power dynamics within the family, feelings of belonging, closeness and/or distance as well as conflict or acknowledgement between family members and the overall attitude family members have toward their context and the critical events they had to face. The application and complete potential of the instrument are further elaborated upon through the presentation of a clinical case. This case not only aids in comprehending the tool’s usage but also enables the collection of psychological information about the family and provides a clinical interpretation of family relationships.